Ductile fracture experiments with locally proportional loading histories. (April 2016) - Roth, Christian C.; Mohr, Dirk
Abstract: Basic ductile fracture experiments for sheet metal (or flat coupons extracted from bulk material) are presented to characterize the onset of fracture at different stress states. Special emphasis is placed on designing the experiments such that the stress triaxiality and the Lode angle parameter remain constant while the specimen is loaded all the way to fracture. A new in-plane specimen with two parallel gage sections is proposed to determine the strain to fracture for approximately zero stress triaxiality. A FEA based methodology is shown to identify the optimal specimen geometry as a function of the material's ductility and strain hardening. A tension specimen with a central hole is investigated in detail with regard to determining the strain to fracture for uniaxial tension. It is found that the required hole-to-ligament width ratio decreases as a function of the material ductility and increases as a function of the strain hardening exponent. The bending of a wide strip is pursued to prevent the necking prior to fracture under plane strain tension conditions, while an Erichsen-type of punch test is used to characterize the material response for equi-biaxial tension. It is worth noting that the strain to fracture can be directly determined from surface strain measurements in the cases of shear, plane strain tension and equi-biaxial tension loading, thereby removing the need to perform finite element simulations for extracting the loading path to fracture.